Does palliative chemotherapy provide a palliative effect on symptoms in late palliative stages? An interview study with oncologists*. (3rd October 2017) - Strang, Peter; Bergqvist, Jenny
Abstract: Background: The possible chemotherapy effects on symptoms in late stages of palliative chemotherapy are seldom registered in clinical practice or investigated as primary outcomes. The aim was therefore to study physicians' opinions and experiences about chemotherapy effects on symptoms. Material and methods: Thirty-five physicians (mainly oncologists) with variation as regards age, gender and experience were included in a qualitative study with semi-structured interviews. A qualitative content analysis was used for the 30–60 min long interviews. Results: According to all the informants, symptoms were possible to control in successful cases but the chances reduce rapidly with the number of chemotherapy lines. Symptoms possible to control included various types of pain (bone pain, neuropathic cranial as well as meningeal nerve pain, colic pain, "liver" pain, headache and pain from cutaneous metastases); nausea and vomiting caused by obstruction; dyspnoea due to pleural effusions or bronchial obstructions. Also fatigue and B-symptoms were possible targets, as were diagnosis-specific symptom clusters (e.g., liver metastasis causing pain, nausea, tumour fever and night sweats; or head–neck cancers resulting in nerve pain, ulcerations, odour, dysphagia and impaired breathing). Some of the oncologists discussed whether the effects were related to chemotherapy treatment only or partly to premedication with steroids. Despite the claimed effects, the physicians did not keep record on symptoms, they did not evaluate them with validated instruments. Conclusions: Palliative chemotherapy has a substantial potential to reduce agonizing symptoms especially in first line treatments, but the effect is limited in late stages. The actual awareness of and knowledge about situations where the treatment has a reasonable potential, should be improved and symptoms should be monitored during treatment.